Tunable Dielectric Properties in Paraffin-Matrix Metacomposites via Macro-Scale Periodic Stacking of the Functional Fillers. (1st May 2022) - Wang, Yuding; Guo, Xinyue; Han, Bingchen; Zhao, Yehao; Qiu, Tianyu; Zhang, Zidong
Abstract : As electronic devices play an increasingly important role in industry and daily life, the demand for materials with excellent dielectric properties to meet different needs is also increasing. In this paper, the effects of the composition and diameter of functional phases on the dielectric properties are investigated, in which the periodically arranged composites are prepared by gravitational self-assembly and the volume fraction of functional phases is controlled. The results show that the micro capacitor introduced by the periodically arranged functional phase leads to a substantial increase in the dielectric constant of the composites when the content is the same. Changing the particle size of the functional phase can change the micro capacitor's polarity to modulate the dielectric properties. It is worth noting that the introduction of the ceramic phase can effectively regulate the dielectric loss of the composite by introducing a new loss mechanism while maintaining a high dielectric constant. This paper provides a deeper understanding of the dielectric property regulation, which provides new ideas for the special dielectric regulation of electronic devices.